A quality control study on Innovatronix, Incorporated - Canusa, Riezl Myreen; Melivo, Allan; Zarzuela, Rosario Cinderela C. (Diliman, Quezon City College of Engineering, 1997)
Innovatronix, Incorporated (iX) is an electronic company engaged in Industrial Automation and Controls. They offers services such as design, testing and installation of custom made systems. They perform Research and Development projects on products that are believed to be useful in the industry. iX manufactures TRONIX off-the-shelf products, timers, displays, and electronic R&D products. The team, through interviews and immersion visits, assessed the company's quality program and how it is implemented. The team found out that Innovatronix does not conduct any incoming inspection or acceptance sampling when receiving their components from their suppliers. Thus the quality of their incoming components depend on the reliability of their vendors and the name brand of their components. The team also found out that AVRs have the most number of factory defectives. Defects usually result as 2 to 3% of the entire production run for a given time range. Certain components are seen to fail more often in some AVR product line models than in others. AVR. failures may be attributed to the following causes: 1.Design, 2.Substandard components, 3.Product misuse. In terms of quality activities, Innovatronix has an edge i design and product development and measuring and testing techniques. Upon completion of the study, the team set forth the following immediate recommendations: a)Evaluation and improvement design with regards to defective components; b)Improve quality data collection by having a Product Failure Summary Table and a Production Sheet, c) Quantify quality goals.
Feasibility Study
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial Quality Control
Keywords: Innovatronix Incorporated; Electronic industries; Quality control